Disrupting intertextual power networks: challenging literature in schools. Issue 6 (2nd November 2022) - Truman, Sarah E.; McLean Davies, Larissa; Buzacott, Lucy
ABSTRACT: This paper thinks with the concept of intertextuality to consider the multiple intersecting power structures inside and outside of literary education in secondary schools that continue to dominate text selection policies and teaching practices. We draw on our research with in-service teachers to reconsider how intertextual networks circulate on multiple levels: textual, social, cultural, and institutional. Although the concept of intertextuality has been activated as an alternative to rarified conceptualisations of literary heritage, as we unpack in this paper, intertextuality often distributes, reinforces, and perpetuates canonical power structures such as institutional whiteness, and Euro western values in secondary school subjects that feature literary studies. Rather than abandoning intertextuality, we attempt to tease out how it operates in various registers in schooling and we suggest how critically engaging with the concept might provide a way forward for English study in the twenty-first century.